Journal information - Carl Edlund Anderson (Universidad de La Sabana, 2014)
The Latin American Journal of Content & Language Integrated Learning (LACLIL) is a no-fee, open-access, peer-reviewed journal focused on CLIL (Content and Language Integrated Learning), multilingualism, multilingual education, languages for special purposes, interculturality, and CALL (computer-assisted language learning) throughout Latin America and around the world aimed at teachers, researchers, and educational administrators who are interested in researching, implementing, or improving language-learning approaches, techniques, materials, and policies.